2020
DOI: 10.1002/jper.20-0434
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin improves periodontitis‐induced kidney damage by decreasing inflammatory stress and apoptosis in rats

Abstract: Background Two main aims of this animal study were to inspect the possible effects of periodontitis on the structure and functions of the kidneys and the therapeutic effectiveness of melatonin. Methods Twenty‐four male Sprague‐Dawley rats were randomly divided into three groups: control, experimental periodontitis (Ep), and Ep‐melatonin (Ep‐Mel). Periodontitis was induced by placing 3.0‐silk sutures sub‐paramarginally around the cervix of right‐left mandibular first molars and maintaining the sutures for 5 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(68 citation statements)
references
References 49 publications
(128 reference statements)
7
59
0
Order By: Relevance
“…with significant increases in MDA, TOS, and OSI associated with kidney damage in rats with experimental periodontitis. 12 Similarly, França et al 13 reported an increase in kidney MDA and OSI levels in rats with periodontitis, and Tomofuji et al 38 reported a higher level of kidney oxidative stress in experimental periodontitis. The results of the present study, consistent with the aforementioned studies, showed higher levels of oxidative stress in the experimental periodontitis group that could be associated with kidney damage.…”
Section: Ta B L E 2 Semiquantitative Analysis Results (Median ± Interquartile Range [25 Percentile-75 Percentile]mentioning
confidence: 97%
See 3 more Smart Citations
“…with significant increases in MDA, TOS, and OSI associated with kidney damage in rats with experimental periodontitis. 12 Similarly, França et al 13 reported an increase in kidney MDA and OSI levels in rats with periodontitis, and Tomofuji et al 38 reported a higher level of kidney oxidative stress in experimental periodontitis. The results of the present study, consistent with the aforementioned studies, showed higher levels of oxidative stress in the experimental periodontitis group that could be associated with kidney damage.…”
Section: Ta B L E 2 Semiquantitative Analysis Results (Median ± Interquartile Range [25 Percentile-75 Percentile]mentioning
confidence: 97%
“…24,25 It is yet unknown exactly with which mechanisms periodontitis increases the risk of kidney disease. This phenomenon has been sought to be explained by the possible effects of oxidative stress 12,13 or systemic inflammatory changes. 7 In both human 35 and animal, 36,37 studies reported that levels of oxidative status parameters such as MDA, GSH, and OSI(TOS/TAS) change, and especially, the levels of OSI, TOS, and MDA increase in kidney damage.…”
Section: Ta B L E 2 Semiquantitative Analysis Results (Median ± Interquartile Range [25 Percentile-75 Percentile]mentioning
confidence: 99%
See 2 more Smart Citations
“…It can be assumed that the development and progression of periodontitis can lead to changes in the form of renal tissue. In another study, three groups of male Wistar rats had their upper molars ligated for 3 weeks to induce periodontitis ( Kose et al, 2020 ). One group of rats was treated with melinjo resveratrol, one without resveratrol, and the other was a control group with no periodontitis or resveratrol treatment.…”
Section: Association Between Pd and Ckdmentioning
confidence: 99%